2013
DOI: 10.1002/phar.1295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacy Services in Heart Failure: An Opinion Paper from the Heart Failure Society of America and American College of Clinical Pharmacy Cardiology Practice and Research Network

Abstract: Heart failure (HF) care takes place in multiple settings, with a variety of providers, and generally involves patients who have multiple comorbidities. This situation is a "perfect storm" of factors that predispose patients to medication errors. The goals of this paper are to outline potential roles for clinical pharmacists in a multidisciplinary HF team, to document outcomes associated with interventions by clinical pharmacists, to recommend minimum training for clinical pharmacists engaged in HF care, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 126 publications
1
74
0
Order By: Relevance
“…18 The impact of clinical pharmacist participation in chronic diseases management programmes has been proven. 19 However, a 2009 ACC survey demonstrated that many cardiologists are unfamiliar with the application of a healthcare team approach to patient care including clinical pharmacists. 20 Unfortunately, the role of clinical pharmacists in managing acute coronary syndrome patients is still underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…18 The impact of clinical pharmacist participation in chronic diseases management programmes has been proven. 19 However, a 2009 ACC survey demonstrated that many cardiologists are unfamiliar with the application of a healthcare team approach to patient care including clinical pharmacists. 20 Unfortunately, the role of clinical pharmacists in managing acute coronary syndrome patients is still underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recent studies reiterate positive HF outcomes by pharmacist interventions in reducing emergency department visits, and all-cause readmissions. 24…”
Section: Pharmaceutical Care In Improving Hf Outcomesmentioning
confidence: 99%
“…[59][60][61] A number of recent publications provide additional insights on the positive impact pharmacists have in the management of HF. [62][63][64] One group 63 reviewed the importance of clinical pharmacists on multidisciplinary teams for inpatient, outpatient, and transplant management of patients with HF. They found that pharmacists improve the care of patients with HF by not only improving adherence to performance measures and evidence-based drug therapies, decreasing readmission rates, and assessing and providing solutions for barriers to medication access, but also through supplementation of activities of the other team members through disbursement of patient education on medication-related topics.…”
Section: Role Of the Pharmacistmentioning
confidence: 99%